Targeting citrullination in autoimmunity: insights learned from preclinical mouse models. (3rd April 2021) - Bruggeman, Ylke; Sodré, Fernanda M.C.; Buitinga, Mijke; Mathieu, Chantal; Overbergh, Lut; Kracht, Maria J.L.
ABSTRACT: Introduction: Aberrant citrullination and excessive peptidylarginine deiminase (PAD) activity are detected in numerous challenging autoimmune diseases such as rheumatoid arthritis, inflammatory bowel diseases, systemic lupus erythematosus, multiple sclerosis, and type 1 diabetes. Because excessive PAD activity is a common denominator in these diseases, PADs are interesting potential therapeutic targets for future therapies. Areas covered: This review summarizes the advances made in the design of PAD inhibitors, their utilization and therapeutic potential in preclinical mouse models of autoimmunity. Relevant literature encompasses studies from 1994 to 2021 that are available on PubMed.gov. Expert opinion: Pan-PAD inhibition is a promising therapeutic strategy for autoimmune diseases. Drugs achieving pan-PAD inhibition were capable of ameliorating, reversing, and preventing clinical symptoms in preclinical mouse models. However, the implications for PADs in key biological processes potentially present a high risk for clinical complications and could hamper the translation of PAD inhibitors to the clinic. We envisage that PAD isozyme-specific inhibitors will improve the understanding the role of PAD isozymes in disease pathology, reduce the risk of side-effects and enhance prospects for future clinical translation.